Energy‐efficient charge‐recovery switching scheme for dual‐capacitive arrays SAR ADC. Issue 5 (1st February 2013) - Li, Y.; Zhang, Z.; Lian, Y.
Abstract : Proposed is an energy‐efficient charge‐recovery switching scheme for a dual‐capacitive arrays successive approximation register (DCA‐SAR) analogue‐to‐digital converter (ADC). With the use of the charge‐recovery technique in a fully differential DCA‐SAR architecture, the proposed switching scheme achieves 98.7 and 46.9% reduction in switching energy and area, respectively, while maintaining the switching energy constant for different output codes.